2020
DOI: 10.1021/acs.jpcc.0c07881
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-Induced High-κ Dielectric Properties and Multiple Phase Transitions between Novel Nonperovskite and Perovskite Phases in LiSbO3: A First-Principles Study

Abstract: The pressure effects on LiSbO3 have been investigated via first-principles simulation. Multiple pressure-induced reconstructive phase transitions between nonperovskite and perovskite states are revealed, i.e., undergoing Pncn-to-R3c-to-P6322-to-Sb:A Pnma-to-P63/m phase transitions with increasing pressure. New nonperovskite P6322 and P63/m states, not present on experiment, can form a reversible transformation (belonging to displacive-/quasi-reconstructive transition in nature) with the increase and decrease o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…On the other hand, recent studies have suggested hydrostatic pressure as a green and effective method to effectively tune the crystal structure, improve the optoelectronic properties, and even make the material metalized to produce superconductivity. As an example, Tian et al found that the crystal structure underwent a transition from a perovskite state to a post-post-perovskite state under hydrostatic pressure accompanied by significant piezochromic effects . In addition, Ke et al verified the piezochromic effects of CsPbI 3 in a high-pressure experiment .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, recent studies have suggested hydrostatic pressure as a green and effective method to effectively tune the crystal structure, improve the optoelectronic properties, and even make the material metalized to produce superconductivity. As an example, Tian et al found that the crystal structure underwent a transition from a perovskite state to a post-post-perovskite state under hydrostatic pressure accompanied by significant piezochromic effects . In addition, Ke et al verified the piezochromic effects of CsPbI 3 in a high-pressure experiment .…”
Section: Introductionmentioning
confidence: 99%
“…16 Rich structural phase transitions can appear in LiSbO 3 at different pressures with large static dielectric tensor and insulating properties. 17 LiSbO 3 with a R3c structure has a large bandgap and mainly absorbs ultraviolet light according to our recent study. 18 LiBiO 3 with the Pccn space group can be prepared via the hydrothermal treatment method.…”
Section: Introductionmentioning
confidence: 72%
“…The elasticity coefficient of R 3 c -LiSbO 3 calculated using the PBE function is smaller than that of the SCAN function (Table 2), 18 and the elasticity coefficient becomes larger under high pressure conditions according to reports in the literature. 17,18 All elasticity coefficients of R 3 c -LiSbO 3 and R 3-Li 2 SbBiO 6 in Table 2 meet the stability conditions. The eigenvalue matrices of the elastic coefficients of LiSbO 3 and Li 2 SbBiO 6 in Table 3 are greater than 0 and satisfy the mechanical stability condition.…”
Section: The Stability Of Li2sbbio6mentioning
confidence: 86%